Strategies for the revitalization of the watercourse landscapes: a case study of the Lielupe river - Vugule, Kristīne; Cērps, Kaspars (Landscape Architecture and Art, 2025)
River tourism is a popular type of recreation across the globe. There is a strong tradition of river tourism in Latvia, mainly boating and rafting in wildlife areas. Zemgale district, with its slowly flowing rivers and predominantly agricultural landscape, is not among the most popular boating destinations. However, the main river of Zemgale – Lielupe River has a tremendous history of river shipping traffic, which nowadays is largely neglected. Seeking a way to revive this kind of river traffic, this paper examines the river’s forces on human society to find a way of river traveling that is compatible with ecological and human comfort necessities. The territory of the Lielupe River floodplain section from Bauska to Sloka towns is characterized according to a travel perspective, considering a passage both on the river and alongside it. The sustainability of the territory is analyzed from the aspects of accessibility, attractiveness, and environmental quality. Since river travel is not imaginable without public access to the riverbank, this paper discusses the development of public waterfronts. It proposes examples of tourist routes along the river and the development of public infrastructure for shipping and boating. The places and character of primary development are considered. The research fits in the framework of the policy of sustainable development of the Latvian countryside.